2016
DOI: 10.1039/c6cp05460a
|View full text |Cite
|
Sign up to set email alerts
|

Hydration in silica based mesoporous materials: a DFT model

Abstract: The MCM-41 material is very commonly used as a support for catalysts. However, theoretical investigations are significantly limited due to the lack of appropriate models that well and accurately describe the real material and enable effective computation at the same time. In this work, our aim is to obtain calculable models at the DFT level of MCM-41 which are as close as possible to the real material. In particular the hydration degree has been investigated, and we present and characterize here for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 117 publications
3
41
0
Order By: Relevance
“…Following the Zhuravlev model, at 400 °C, the silanol concentration on the silica surface is below 2 OH/nm 2 . More recently, Gierada et al have proposed a new model that gives a concentration between 3.6 and 1.7 OH/nm 2 for water pressure from 10 –2 to 10 –9 atm, at 400 °C. One can thus assume that the silica is only poorly hydroxylated at the interface with the nanoparticles, validating the choice of a dehydroxylated silica surface in our models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the Zhuravlev model, at 400 °C, the silanol concentration on the silica surface is below 2 OH/nm 2 . More recently, Gierada et al have proposed a new model that gives a concentration between 3.6 and 1.7 OH/nm 2 for water pressure from 10 –2 to 10 –9 atm, at 400 °C. One can thus assume that the silica is only poorly hydroxylated at the interface with the nanoparticles, validating the choice of a dehydroxylated silica surface in our models.…”
Section: Discussionmentioning
confidence: 99%
“…The low-energy range allows the formation of a 2D array of AgNPs at a nanometer distance from the SiO 2 free surface (Figure b) . In our previous experiments, the samples were further annealed under a N 2 atmosphere at a temperature of 500 °C for damage recovery, and it has been shown that thermal treatment of the silica surface leads to partial dehydroxylation of the surface for temperatures above 400 °C and to complete dehydroxylation for temperatures as high as 1000 °C. In addition, the effect of the temperature during annealing should lead to a higher reactivity of the silica surface toward the metallic nanoparticles. It is therefore most likely that direct chemical bonding between the AgNP surfaces and the silica matrix could exist.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, desorption times resulted as To evaluate the stability of the surfaces in the presence of adsorbed carbon monoxide, we computed the surface free energies G S according to the following expression which is derived from first principle thermodynamics. E S is the surface energy computed according to eq , BE is the dispersion-BSSE-corrected binding energy per adsorbed molecule. T , P , and P θ are the absolute temperature, the partial pressure of CO, and the standard pressure (= 101325 Pa).…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, the interaction with the wall of the MCM-41 tends to drive the OTS to become attached to the framework, at least at this OTS density, since one would expect more intermolecular contact at higher OTS densities. Note that in this model of MCM-41, the wall is rather hydrophilic, with a surface OH density of 5.8 per nm 2 . The driving force for the OTS to lean toward the MCM-41 framework seems to be the van der Waals interactions.…”
Section: Resultsmentioning
confidence: 93%